ETIKA KEPEMIMPINAN DAUD DALAM 1 TAWARIKH 29:10-13: KAJIAN EKSEGETIS DAN RELEVANSINYA BAGI KEPEMIMPINAN KONTEMPORER - Benediktus James Widya Darmaka; Edi Zakarijah; Herman Sjahthi; Andreas Andry Handiyanto (RERUM: Journal of Biblical Practice, 2026)
AbstractThis study explores the ethical leadership principles derived from the Book of 1 Chronicles, focusing on the examples of leadership portrayed in the text. The background of the problem lies in the contemporary challenges faced by leaders in both public and private sectors, where ethical dilemmas frequently arise. The objective of this research is to identify and analyze the spiritual and moral values of leadership in 1 Chronicles and their applicability in modern leadership contexts. The methodology employed includes hermeneutic analysis and literature review, examining relevant biblical texts and contemporary leadership theories. The findings suggest that the values of humility, accountability, and service exemplified in 1 Chronicles can significantly enhance ethical leadership practices today. This research contributes to the discourse on leadership ethics by providing practical insights for contemporary leaders grounded in timeless spiritual principles.   AbstrakPenelitian ini mengeksplorasi prinsip-prinsip etika kepemimpinan yang diambil dari Kitab 1 Tawarikh, dengan fokus pada contoh-contoh kepemimpinan yang ditampilkan dalam teks. Latar belakang masalah terletak pada tantangan kontemporer yang dihadapi oleh para pemimpin di sektor publik dan swasta, di mana dilema etika sering muncul. Tujuan penelitian ini adalah untuk mengidentifikasi dan menganalisis nilai-nilai spiritual dan moral dalam kepemimpinan yang terdapat dalam 1 Tawarikh dan penerapannya dalam konteks kepemimpinan modern. Metodologi yang digunakan meliputi analisis hermeneutik dan tinjauan literatur, dengan mengkaji teks-teks alkitabiah yang relevan dan teori kepemimpinan kontemporer. Temuan menunjukkan bahwa nilai-nilai kerendahan hati, akuntabilitas, dan pelayanan yang dicontohkan dalam 1 Tawarikh dapat secara signifikan meningkatkan praktik etika kepemimpinan saat ini. Penelitian ini memberikan kontribusi pada diskursus etika kepemimpinan dengan menawarkan wawasan praktis bagi pemimpin masa kini yang berlandaskan pada prinsip-prinsip spiritual yang abadi.